ANALYSIS OF THE IMPLEMENTATION OF NON-PROFIT ORGANIZATION FINANCIAL REPORTS BASED ON PSAK NO. 45 AT THE PUNDI AMAL PEDULI KASI FOUNDATION - Asrah Tandirerung Ranteallo; Niken Herawati; Ade Sri Mulyani (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
The implementation of Financial Accounting Standards (PSAK) plays a crucial role in the preparation of financial statements for non-profit organizations, including foundations. This study aims to analyze the application of financial reporting for non-profit organizations based on PSAK No. 45 at the Yayasan Pundi Amal Peduli Kasih. The results of this research are expected to serve as a reference for the foundation in preparing accountable and transparent financial statements in accordance with the applicable standards in Indonesia. This study employs a qualitative approach using secondary data obtained from the foundation’s financial statements. The financial management process of the foundation involves collecting funds from donors who contribute without expecting any financial return. The analysis shows that the accounting system applied records the receipt and disbursement of funds, which are subsequently summarized to prepare monthly financial reports. The findings indicate that the foundation’s financial statements remain relatively simple and have not yet fully complied with PSAK No. 45 on the financial reporting of non-profit organizations. Therefore, improvements are needed in the application of accounting standards to ensure that the foundation’s financial statements are presented more transparently and in accordance with generally accepted accounting principles.